Mixed epithelial and stromal tumor of the kidney (MEST) simulating - Sountoulides, Petros; Koptsis, Michail; Metaxa, Linda; Theodosiou, Alexandros; Kikidakis, Dimitrios; Filintatzi, Chrysa; Paschalidis, Konstantinos (Canadian Urological Association Journal, 2013)
We present a rare and interesting case of a mixed epithelial and stromal tumour (MEST) of the kidney. The case is unique as it involves a male patient with no history of hormonal therapy presenting with a filling defect in the renal collecting system and positive urine cytology. The patient was diagnosed with transitional cell carcinoma of the renal pelvis and subjected to nephroureterectomy, which revealed a solid tumour arising from the lower calyces and extending into the renal pelvis and upper ureter. Pathology revealed a MEST. The patient was disease-free at the 6-month follow-up.